2023
DOI: 10.3390/molecules28114531
|View full text |Cite
|
Sign up to set email alerts
|

New Insight on In Vitro Biological Activities of Sulfated Polysaccharides from Ulvophyte Green Algae

Abstract: Green algae are natural bioresources that have excellent bioactive potential, partly due to sulfated polysaccharides (SPs) which are still rarely explored for their biological activities. There is currently an urgent need for studies exploring the anticancer biological activity of SPs extracted from two Indonesian ulvophyte green algae: the sulfated polysaccharide of Caulerpa racemosa (SPCr) and the sulfated polysaccharide of Caulerpa lentillifera (SPCl). The method of isolating SPs and their assessment of bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…These polysaccharides also enhance insulin signaling pathways by acting on insulin receptors and activating the PI3K/Akt pathway, ultimately regulating the ERK/JNK/MAPK pathway [ 17 ]. Furthermore, type B ulvanobiuronicacid 3-sulfate—a member of polysaccharide ulvan—was also characterized and might contribute to the beneficial health properties of Caulerpa racemosa SPs [ 12 ]. In conjunction with that, the authors’ previous work demonstrated that Caulerpa racemosa SPs have anti-obesity, antiaging, antidiabetic, and antioxidant properties [ 12 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These polysaccharides also enhance insulin signaling pathways by acting on insulin receptors and activating the PI3K/Akt pathway, ultimately regulating the ERK/JNK/MAPK pathway [ 17 ]. Furthermore, type B ulvanobiuronicacid 3-sulfate—a member of polysaccharide ulvan—was also characterized and might contribute to the beneficial health properties of Caulerpa racemosa SPs [ 12 ]. In conjunction with that, the authors’ previous work demonstrated that Caulerpa racemosa SPs have anti-obesity, antiaging, antidiabetic, and antioxidant properties [ 12 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, type B ulvanobiuronicacid 3-sulfate—a member of polysaccharide ulvan—was also characterized and might contribute to the beneficial health properties of Caulerpa racemosa SPs [ 12 ]. In conjunction with that, the authors’ previous work demonstrated that Caulerpa racemosa SPs have anti-obesity, antiaging, antidiabetic, and antioxidant properties [ 12 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations